Semiotika Atribut Sebagai Pesan Komunikasi: Studi Kasus Atribut Ibu Anggota DPR RI - Tulasi, Dominikus (Humaniora, 2014)
Research aims to know denotative and connotative meaning of the attributes used by female members of House of Representatives as an integrated signifier and signified in their appeance. In terms of the research context “performance” was “sign” itself, by seeking the new structure existing in the attribute of their appearance. Attribute denotative meaning is the overall objects seemed. Connotative meaning is the meaning existing fits to the context of local culture, within it loads particular human being expression individually. The method used in the study is inductive-posteriori-explorative-qualitative, with a case study using semiotic analysis of communication led to internalization of the researcher towards the phenomenon of attributes used by the female members of the House of Representatives. The choice and use of attributes in each appearance can be used to give impressions used an anchor by the researcher to provide further interpretation of the attributes worn. This study took the paradigm theory of Ferdinand de Saussure and Charles Sanders Peirce to see through its problems in the field. The result is Saussure’s view is able to reconstruct all objects visible to the researcher. Similarly, Peirce's view has three major characteristics that are capable of being a mirror to see the reality in the field. The results showed an attempt to reconstruct the understanding of semiotics and attributes as a form of nonverbal communication message. The study concludes the denotative meaning of attributes can provide communication and connotative message over the attributes used by female members of the Parliament.